2020
DOI: 10.1111/ijlh.13315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the BD Stem Cell Enumeration Kit on the BD FACSCanto II flow cytometer using bd facscanto clinical and bd facsdiva software

Abstract: Transplantation of hematopoietic stem cells (HSC) has been a widely used therapeutic option in patients with hematologic malignancies, congenital or acquired bone marrow failure, immunodeficiency states and autoimmunity for decades. 1 Peripheral blood has become the most commonly used source of HSC in both autologous and allogeneic transplantation due to easier accessibility and faster engraftment. Peripheral blood stem cells (PBSC) are collected with leukapheresis procedure, preceded by mobilization of HSC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Sample stability study is an important part of validation of the protocol used for quality assessment, especially when implementing a new type of cell therapy product. Several studies have examined the stability of fresh leukapheresis samples and thawed cryopreserved UCB samples 37,39,54,55 . The results showed that fresh leukapheresis samples were stable up to 24 h stored at 4°C 37,39 .…”
Section: Quality Control and Validation Of Flow Cytometry Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sample stability study is an important part of validation of the protocol used for quality assessment, especially when implementing a new type of cell therapy product. Several studies have examined the stability of fresh leukapheresis samples and thawed cryopreserved UCB samples 37,39,54,55 . The results showed that fresh leukapheresis samples were stable up to 24 h stored at 4°C 37,39 .…”
Section: Quality Control and Validation Of Flow Cytometry Methodsmentioning
confidence: 99%
“…Several studies have examined the stability of fresh leukapheresis samples and thawed cryopreserved UCB samples 37,39,54,55 . The results showed that fresh leukapheresis samples were stable up to 24 h stored at 4°C 37,39 . The results of stability studies of thawed UCB samples were conflicting.…”
Section: Quality Control and Validation Of Flow Cytometry Methodsmentioning
confidence: 99%
See 3 more Smart Citations